Maximilien Robespierre and the French Revolution - Schmermund, Elizabeth; McGowen, Tom. (New York, NY Enslow Publishing, 2016)
"Describes the life of Maximilien Robespierre and his influence on the French Revolution"--
The guillotine -- L'Ancien Regime -- Revolutionary rumblings -- The storming of the Bastille -- Freed citizens and a captive king -- Political disagreements and a desperate escape attempt -- The end of the monarchy -- The death of citizen Louis Capet -- Civil War -- The reign of terror -- Legacy of the French Revolution.
Includes bibliographical references (pages 121-124, 126) and index.
Grade 7 to 8.
12-up.
108246
Keywords: Robespierre, Maximilien, -- 1758-1794 -- Juvenile literature; 1789-1799; Revolutionaries -- France -- Biography -- Juvenile literature; France -- History -- Revolution, 1789-1799 -- Juvenile literature; France -- History -- Reign of Terror, 1793-1794 -- Juvenile literature; Literature; Biographies; History; Juvenile works